Tumour grade and stage are associated with specific body composition phenotypes with visceral obesity predisposing the host to a less aggressive tumour in colorectal cancer. Issue 7 (July 2022) - Pring, Edward T.; Malietzis, George; Gould, Laura E.; Lung, Philip; Drami, Ioanna; Athanasiou, Thanos; Jenkins, John T.
Abstract: Background: Sarcopenia, myosteatosis and visceral obesity (VO) are known to negatively impact on outcomes from colorectal cancer (CRC). Little is known about tumour factors associated with these body composition (BC) phenotypes. We aimed to identify whether histopathological tumour characteristics were associated with various BC phenotypes. Methods: A prospectively collected database of patients undergoing surgery for primary CRC at a tertiary referral unit in the United Kingdom was analysed. Sarcopenia, myosteatosis and VO were identified on preoperative CT. Binary logistic regression modelling was performed to determine significant associations between tumour stage, grade and BC phenotype. Results: Final analysis included 795 patients; median age 69, 56% male, 65% were sarcopenic, 72% myosteatotic, 52% VO and 20% had sarcopenic obesity (SO). VO patients were significantly less likely to have advanced T Stage (T3-4) OR0.62(95%CI 0.44–0.86, p = 0.005); nodal metastases OR0.60(95%CI 0.44–0.82, p = 0.001); vascular invasion OR0.63(95%CI 0.46–0.88, p = 0.006) and poor tumour differentiation OR0.49(95%CI 0.28–0.86, p = 0.012). Myosteatotic patients were more likely to have metastatic disease OR2.31(95%CI 1.15–4.63, p = 0.018) but less likely to have poorly differentiated tumours OR0.48(95%CI 0.27–0.86, p = 0.013). SO patients were significantly more likely to have poorly differentiated tumours OR2.01(95%CI 1.04–3.87, p = 0.037). Conclusion: VO predisposes to earlier stage tumours with a less aggressive tumour phenotype. The SO group have adverse tumour characteristics which may be explained by differences in fat distribution. Myosteatosis relates to increased likelihood of distant metastasis that may be related to a systemic inflammatory response, despite the association with better differentiated tumours.